Representations of Public Perceptions on Indonesia’s 2024 Presidential Candidates: A Semiotic Analysis of Memes on Social Media - Darlius, Adilla Nadya Soraya; Aprilia, Fitria; Neisya, Neisya (Universitas Pendidikan Mandalika, 2024)
In the context of the 2024 Indonesian presidential election, a new phenomenon has emerged among social media users: the creativity in making memes. These memes, which can take the form of text or images, address issues and events in an evocative style, becoming widely discussed due to their rapid dissemination and commentary on social media. This research aims to describe the signifiers and signifieds in memes related to the 2024 Indonesian presidential and vice-presidential candidates, elucidate the meanings contained in these memes, and explore the connection between memes on social media and the representation of public perception. This study employs a qualitative approach with a case study design by employing semiotic analysis. The markers in these memes include snippets of cartoon and film scenes. The allusions in the memes align with the reality of the Indonesian 2024 presidential and vice-presidential candidate debates. These memes convey statements that contain information and public perceptions regarding the behavior, attitudes, and outcomes of the 2024 Indonesian presidential candidates. The results indicate that public perceptions are represented in the memes of the 2024 presidential candidates, encompassing expressions, perceptions, criticisms, humor, and satire. Furthermore, signifiers and signifieds are identified in each meme. This study reveals that memes play a crucial role in reflecting and shaping public perceptions during the 2024 Indonesian presidential election. Through creative expressions of humour, criticism, and satire, memes capture and communicate public sentiments about the candidates, highlighting their influence as a powerful tool in modern political discourse and public engagement.